2019
DOI: 10.1039/c9sc01299k
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the thermodynamic criteria for responsive adsorption processes

Abstract: A general thermodynamic model to investigate responsive adsorption processes in flexible porous materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 39 publications
(47 reference statements)
1
45
0
3
Order By: Relevance
“…To qualitatively describe potential flexing modes in SPCs, a hinging model was used to determine flexible modes regardless of chemical composition . A toy model approach based on a slit pore was used to explore thermodynamic and kinetic aspects in responsive pores . The interplay between the adsorption properties of PCPs and SPCs with an elastic gas reservoir demonstrated the complex multistability of such a system that may be correlated to gas storage applications …”
Section: Synthesis Characterization and Prediction Of Spcs And Softmentioning
confidence: 99%
“…To qualitatively describe potential flexing modes in SPCs, a hinging model was used to determine flexible modes regardless of chemical composition . A toy model approach based on a slit pore was used to explore thermodynamic and kinetic aspects in responsive pores . The interplay between the adsorption properties of PCPs and SPCs with an elastic gas reservoir demonstrated the complex multistability of such a system that may be correlated to gas storage applications …”
Section: Synthesis Characterization and Prediction Of Spcs And Softmentioning
confidence: 99%
“…In the published literature, DUT-49 and DUT-50 are so far unique in their ability to sustain a guest-overloaded metastable state before they undergo adsorption-induced structural contraction leading to NGA and pressure amplification. According to previous experimental 36 and computational studies, 34 To test the porosity of the bulk materials and potential occurrence of adsorption-induced transitions, the desolvated MOF powders were analysed using nitrogen physisorption at 77 K. Grand Canonical Monte Carlo (GCMC) simulations for op and cp phase greatly facilitate the interpretation of the experimental adsorption isotherms (description of the simulation procedures and CIF files in ESI) (Figure 4). DUT-160 and DUT-161 stand out as highly porous materials with specific pore volumes up to 3.38 and 3.2 cm 3 g -1 and geometrically accessible surface areas of 5342 and 5229 m 2 g -1 , respectively determined by Zeo++ calculations 47 from the simulated crystal structures (Error!…”
Section: Analysis Of Adsorption Properties By Experiments and Simulationmentioning
confidence: 99%
“…Computational analysis showed that this behaviour can in principle be observed for other porous materials if their mechanical properties allow for bistability. 34 We subsequently investigated molecular changes to the DUT-49 structure in an effort to tune or change the inelastic mechanical response involved in this phenomenon. Motivated by the macroscopic understanding of columnar buckling, in recent studies we considered shortening 35 and elongation of the molecular struts.…”
Section: Introductionmentioning
confidence: 99%
“…However, these molecular simulations in a complex pore system, such as DUT-49, are computationally very challenging. Instead, we recently demonstrated that thermodynamic and kinetic conditions for NGA can be modeled in a simple slit-pore toy model 15 .…”
Section: Adsorption Stress Model For Determination Of Low Temperaturementioning
confidence: 99%
“…The step-wise isotherms and switching of the solid is caused by highly inelastic transformations and an anharmonic potential energy function (Helmholtz Free Energy). 15 In recent years especially computational analysis has demonstrated that adsorption-induced structural transitions are a complex interplay between the structural flexibility of the MOF, as well as the solid-fluid and fluid-fluid interactions. [16][17][18] Beyond the nature of the solid and fluid, temperature effects were found to have a large impact on the presence of breathing in systems lie MIL-53 19,20 and ZIF-8 21 , however little experimental and computational work has been performed beyond these systems.…”
Section: Introductionmentioning
confidence: 99%